Iterative multiuser detection using antenna arrays and FEC on multipath channels. - Reed, M.C.
This paper investigates a multiple-access communication receiver system that receives coded data modulated using either direct-sequence code division multiple access or narrowband binary phase shift keying, with an antenna array in a multipath propagation environment. We describe an iterative receiver that improves the initial estimates from the antenna array, and therefore reduces the multiple access interference. Simulation results show that the bit error rate performance approaches that obtained when only one user's signal is incident on the array. This occurs even with a large number of users in comparison to the product of the spreading gain and array size
Keywords: BFSK; DOA; DS-CDMA.; FEC; MAP decoding; Antenna arrays; Bit error rate performance; Coded data modulation; Direct-sequence code division multiple access; Iterative multiuser detection; Iterative receiver; Multipath channels; Multipath propagation environment; Multiple access interference reduction; Multiple-access communication receiver system; Narrowband binary phase shift keying; Simulation results; Spreading gain-array size product